Population:today and tomorrow (Vol.2) Policies, theories and methodologies (Delhi, 1989)
These three volumes contain nearly one hundred papers duly chosen and assessed to meet the scientific objectives SO exemplified. These volumes highlight the most important aspect of population, today and tomorrow. The first and probably the most important objective is to provide a forum at which the International Union for the Scientific Study of Population can present its work. Much of this input does not appear anywhere. The second objective is to include all that is significant, progressive, novel and exciting in current demographic research. In the countless issues on population the common aim has been the pursuit of advancement in the realm of science of demography. In the fight of these selected papers, the main emphasis has been on population issues of Asia within the framework of constraints as well.
Keywords: Population